Mass appeal : the formative age of the movies, radio, and tv - Berkowitz, Edward D. (Cambridge : Cambridge University Press, 2010)
Mass Appeal describes the changing world of American popular culture from the first sound movies through the age of television. In short vignettes, the book reveals the career patterns of people who became big movie, TV, or radio stars. Eddie Cantor and Al Jolson symbolize the early stars of sound movies. Groucho Marx and Fred Astaire represent the movie stars of the 1930s, and Jack Benny stands in for the 1930s performers who achieved their success on radio. Katharine Hepburn, a stage and film star, illustrates the cultural trends of the late 1930s and early 1940s. Humphrey Bogart and Bob Hope serve as examples of performers who achieved great success during the Second World War. Walt Disney, Woody Allen, and Lucille Ball, among others, become the representative figures of the postwar world. Through these vignettes, the reader comes to understand the development of American mass media in the twentieth century.
Machine generated contents note: 1. Sound comes in, vaudeville and silent pictures go out; 2. From Broadway to Hollywood with Groucho, Fred, and Ginger; 3. Radio nights; 4. From the 30s to the 40s with Kate, Bud, and Lou; 5. Bogie, Bob, and the boys at war; 6. The postwar movie scene; 7. Make room for TV; 8. Putting it together: Walt Disney introduces the baby boom to television; 9. The end of an era?
English
Includes bibliographical references and index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Motion pictures -- United States -- History -- 20th century; Radio programs -- United States -- History -- 20th century; Television programs -- United States -- History -- 20th century